Outflows from Insured Unemployment in Hungary, 1992-1996 - Gyula Nagy; Peter Galasi (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 1999)
The paper looks at outflows from registered unemployment in Hungary between 1992 and 1996 using microdata from the unemployment insurance system. We address two questions. First, we investigate the trends in outflows in the period. A related question is whether the decline in the unemployment stock from early 1993 is associated with an increase in the outflow. Second, we look at how the probability of leaving registered unemployment to five states - employment, training, subsidised employment, subsidised self-employment and public works - varies with personal characteristics and the local unemployment rate. This also shows how active labour market policy in Hungary is "targeted" across groups of unemployed.
Keywords: 330